Association of variants of miRNA processing genes with cervical precancerous lesion risk in a southern Chinese population. Issue 3 (31st May 2018) - Huang, Shi-Qi; Zhou, Zi-Xing; Zheng, Shao-Ling; Liu, Dan-Dan; Ye, Xiao-Hong; Zeng, Cheng-Li; Han, Ya-Jing; Wen, Zi-Hao; Zou, Xiao-Qian; Wu, Jing; Liu, Yu-Mei; Huang, Chui-Can; et al.
Abstract : The miRNA processing genes play essential roles in the biosynthesis of mammalian miRNAs, and their genetic variants are involved in the development of various cancers. Our study aimed to determine the potential association between miRNA processing gene polymorphisms and cervical precancerous lesions. Five single nucleotide polymorphisms (SNPs), including Ran-GTP ( RAN ) rs14035, exportin-5 ( XPO5 ) rs11077, DICER1 rs3742330, DICER1 rs13078, and TARBP2 rs784567, were genotyped in a case–control study to estimate risk factors of cervical precancerous lesions. The gene–environment interactions and haplotype association were estimated. We identified a 27% decreased risk of cervical precancerous lesions for individuals with minor G allele in DICER1 rs3742330 (odds ratio (OR) = 0.73, 95% confidence interval (95% CI) = 0.58–0.92, P = 0.009). The AG and AG/GG genotypes in DICER1 rs3742330 were also found to decrease the risk of cervical precancerous lesions (AG compared with AA: OR = 0.51, 95% CI = 0.35–0.73, P <0.001; AG/GG compared with AA: OR = 0.54, 95% CI = 0.39–0.77, P = 0.001). The GT haplotype in DICER1 had a risk effect on cervical precancerous lesions compared with the AT haplotype (OR = 1.36, 95% CI = 1.08–1.73, P = 0.010). A two-factor ( DICER1 rs3742330 and human papillomavirus (HPV) infection) and two three-factor (model 1: rs3742330, passive smoking, and HPV infection; model 2: rs3742330, abortion history, and HPV infection) interaction models for cervical precancerous lesions were identified. In conclusion, the genetic variants in the miRNA processing genes and interactions with certain environmental factors might contribute to the risk of cervical precancerous lesions in southern Chinese women.